COMPARATIVE ANALYSIS OF PRESSURE AND FLOW CHARACTERISTICS IN BASIC AND MODIFIED AIR COMPRESSOR PIPELINE USING COMPUTATIONAL FLUID DYNAMICS IN POWER PLANT TANJUNG ENIM 3X10 MW - Septano, Gurruh Dwi; Ramadhoni, Tri Satya; Sumarna, Herlin (Media Mesin: Majalah Teknik Mesin, 2024)
Air compressor plays a crucial role by converting electrical energy into kinetic energy in the form of compressed air. This study specifically concentrates on assessing the performance of two compressors that operate alternately, with one compressor in standby mode. Unfortunately, compressor unit #1 faced issues with its drying system, rendering it unable to function within the current pipe network. In order to rectify this, proposed modifications to the pipeline network are introduced and scrutinized. To analyze these modifications, Computational Fluid Dynamics (CFD) is employed to evaluate and compare pressure and flow characteristics in both the existing and modified pipe configurations. The CFD analysis utilizes computer engineering software, with SolidWorks serving as the primary modeling and simulation tool. The assumption is made that the Reynolds number corresponds to laminar flow, factoring in pipe diameter and compressor volume rate.The resulting CFD data offers valuable insights into pressure and velocity distributions within the existing and modified pipeline networks. During the pressure simulation, surface pressure and output on both standard and modified pipes exhibit relatively similar pressure values at 7 bar. However, in the air velocity simulation, surfaces of standard and modified pipes maintain a consistent range of 0 – 5 mm/s. Notably, from the pipe output side, air velocity in standard and modified pipes displays distinct speed contours. Standard pipes show the highest speed between 0.25 – 0.38 mm/s, whereas modified pipes exhibit the highest speed within the range of 0.15 – 0.2 mm/s. This study aims to provide a comprehensive evaluation of the proposed modifications, seeking to enhance understanding of the fluid dynamics within air compressor systems. The outcomes of this research have the potential to contribute significantly to optimizing the performance and efficiency of these systems, thereby offering benefits across various industrial applications.